PENINGKATAN PEMAHAMAN KONSEP MATEMATIS MELALUI PENERAPAN MODEL PEMBELAJARAN TREFFINGER BERBANTU BAHAN AJAR ALQURUN (Improving the Understanding of Mathematic Concepts through the Application of Treffinger Learning Model Assisted with Alqurun Teaching Materials) - Hezvi Yulinsa; Rizki Wahyu Yunian Putra; Farida Farida (Universitas Islam Negeri Ar-Raniry, 2021)
The background of this research is the students' low understanding of mathematical concepts. The purpose of this study is to improve understanding of mathematical concepts through the Treffinger learning model assisted by ALQURUN teaching materials. The research method used is a quantitative method with the type of Quasi Experimental Design research with stages 1) pre-test (initial data) 2) treatment (treatment) 3) post-test (final data). The population in this study were students of class X IPA MAN 1 Pringsewu, with a sample consisting of three experimental classes and one control class. Based on data analysis, the increase in understanding of mathematical concepts in the experimental class and control class varies. The difference in the increase in the ability to understand this concept was then tested statistically with the one-way ANOVA test with a significant level. Based on the N-Gain test, it was concluded that the average increase in understanding mathematical concepts by applying the Treffinger learning model assisted by ALQURUN teaching materials was higher, namely 0.84 compared to with the class that applied the Treffinger learning model with an average of 0.66, the class that applied the conventional learning model assisted with ALQURUN teaching materials with an average of 0.43 and the class that applied the conventional learning model with an average of 0.14. Based on the average ability to understand mathematical concepts, it can be concluded that the Treffinger learning model with ALQURUN teaching materials is better than the Treffinger learning model, the conventional learning model assisted by ALQURUN teaching materials and conventional learning models.